Digital-Based Logma Educational Game on Early Childhood Logic-Mathematics Intelligence - Andesta, Dini; Muhtarom, Muhtarom; Sartika, Indah Dwi; Wahyuni, Desvi; Febrianti, Febrianti; Dewi, Kurnia (UPI Kampus Cibiru, 2024)
This research aims to improve early childhood Logic-Mathematics Intelligence and create a valid and practical Logma Educational Game Media by using the ADDIE development research approach (analysis, design, development, implementation, and evaluation). The data collection procedures used documentation, interviews, questionnaires, and observations. Validity and practicality tests were used in the data analysis process. Data related to validity and practicality were obtained from questionnaire answers, which were then analyzed using a Likert scale. Based on the results of the study, the validity of material experts I is 82.2 very valid level, the material II 93.3 very valid category, and the media experts 96.6 very valid level. The practicality test of the Logma Educational Game based on the teacher response questionnaire 86.2 level is very practical, as well as a small-scale trial learner instrument questionnaire 96 declared very practical and a large-scale trial 93.1 declared very practical. The results of this study conclude that the digital-based Logma Educational Game to increase Logical-Mathematical Intelligence is declared valid, practical, and feasible to use in learning. The impact of the Logma Educational Game on technological progress is that it can be use as a means of learning mathematics that can help children understand the concept of logic-mathematics from an early age, so that when entering elementary school children no longer feel afraid to learn mathematics.